Low-wage employment - Claus Schnabel (IZA World of Labor, 2016)
Low-wage employment has become an important feature of the labor market and a controversial topic for debate in many countries. How to interpret the prominence of low-paid jobs and whether they are beneficial to workers or society is currently an open question. The answer depends on whether low-paid jobs are largely transitory and serve as stepping stones to higher-paid employment, whether they become persistent, or whether they result in repeated unemployment. The empirical evidence is mixed, pointing to both stepping-stone effects and “scarring” effects (i.e. long-lasting detrimental effects) of low-paid work.
Keywords: J30; J31; J21; 330; low-wage employment; wages; stepping stone; state dependence